Impact of Digital Technologies on the Labour Market - Počepavičiūtė, Raminta; Kiaušienė, Ilona (Vilnius University Proceedings, 2025)
Such innovations as blockchain, artificial intelligence, and the Internet of Things exhibit an increasing impact on different sectors of the economy. These changes are creating new jobs while simultaneously changing the nature of work, demanding new skills, and reducing the demand for traditional jobs. The aim of the research is to identify the impact of digital technologies on the labour market. The results show that the implications of digital technologies for the labour market and employment of workers are analysed from different perspectives. The rapid development of digital technologies promotes innovation, leading to faster job creation in the labour market. On the other hand, technological processes lead to fewer jobs, which will increase unemployment. There are also those who believe that society will not notice major changes in the labour market because technological progress will create as many jobs as it will eliminate.
Keywords: digital technologies; labour market; employment; trends